Diagnostic Benefit of Simultaneous Capsule Endoscopy Using Two Different Systems. (28th May 2018) - Kim, Seung Han; Choi, Hyuk Soon; Chun, Hoon Jai; Kim, Eun Sun; Keum, Bora; Seo, Yeon Seok; Jeen, Yoon Tae; Lee, Hong Sik; Um, Soon Ho; Kim, Chang Duck
Abstract : Background/Aims . Capsule endoscopy (CE) is a noninvasive test for diagnosing small bowel disorders. However, several studies reported that the CE-based visualization is suboptimal. This study, the first to use two CEs simultaneously, aimed at evaluating the diagnostic ability of dual CE. Methods . Dual CE procedures were prospectively conducted. All patients completed bowel cleansing 2 hours before examination. Subsequently, they simultaneously swallowed two capsules: MiroCam (IntroMedic, Seoul, Korea) and PillCam SB3 (Medtronic, Minneapolis, USA). We assessed the completeness and feasibility of small bowel examination and the detection rate of duodenal papilla and diagnostic yield. Results . Twenty consecutive patients who underwent complete small bowel examination with dual CE were enrolled in the study. The mean time of small bowel passage was 245 ± 99 min. Dual CE examination increased the duodenal papilla detection rate to up to 75% (versus PillCam SB3 alone (P = 0.031 ) and MiroCam alone (P = 0.063 )) and overall diagnostic yield to up to 70% (P = 0.063 ) in comparison to single CE. Adverse events or electrical interference during data transmission between the two capsule endoscopes were not detected. Conclusions . In this study, we found that dual CE enhances diagnostic accuracy and could increase the diagnostic power of existing CE systems using simply applicable methods. This trial is registered with KCT0002541 .